Long‐term safety of replication‐defective smallpox vaccine (MVA‐BN) in atopic eczema and allergic rhinitis. (29th June 2016) - Darsow, U.; Sbornik, M.; Rombold, S.; Katzer, K.; von Sonnenburg, F.; Behrendt, H.; Ring, J.
Abstract: Background: Availability of a safe smallpox vaccine may be necessary under certain circumstances. Use of the old life virus vaccine was associated with serious adverse events, particularly in the setting of atopic eczema (AE) and immunodeficiency. Modified virus Ankara (MVA)‐BN, a highly attenuated strain of vaccinia virus, was developed for vaccination with improved safety profile. Methods: A phase 1 study was conducted in 60 subjects without history of smallpox vaccination to gain experience with smallpox vaccination using this strain in healthy and atopic subjects. Healthy subjects, subjects with a history of AE, subjects with mild active AE and subjects with mild allergic rhinitis without AE were equally allocated into four groups. MVA‐BN was injected s.c. in a dose of 10 8 TCID50 twice in a 4‐week interval. Results: No serious or unexpected adverse reactions were reported. All subjects experienced mild to moderate pain and redness at the injection site. Dermatologic examinations did not reveal any unfavourable reactions to the study medication, particularly no sign or exacerbation of eczema for as long as 196 days. All subjects seroconverted after two vaccinations and no significant difference in antibody titres between the four different groups was observed. Conclusions: A good safety profile of the MVA‐BN vaccine was shown. The absence of adverse events in subjects with atopic disorders appears promising for the development of a safe smallpox vaccine for patients with AE or other atopic diseases.